Harmonization of Law No. 11 of 2010 concerning Cultural Heritage in the Preservation of Cultural Heritage Objects of Semarang City - Prabowo, M. Shidqon; Kustanto, Anto (Faculty of Law, Universitas Negeri Semarang, 2019)
The Semarang City Government has been criticized by the community because it is considered to allow the demolition of ancient and historic buildings to be replaced with new buildings that are economically more profitable. The city has ancient buildings of high historical and architectural value, especially in the Old City cultural heritage area. Blenduk Church, for example, which was built in 1742, is a landmark of the Old City. Therefore, the following problems can be formulated: (1) What is the existence of Cultural Heritage objects in the city of Semarang? (2) What about Law No. 11 of 2010 in providing protection for Semarang City Cultural Heritage Property?, (3) What are the obstacles in implementing the preservation of Cultural Heritage objects in Semarang City? The method used in the socialization and dissemination of law regarding Law No.11 of 2010 concerning Cultural Heritage conducted at the activity participants is a lecture, question and answer, and discussion model. The results of the community service activities show that there is an increase in understanding and knowledge of the community service participants, which is indicated by the results of tests conducted by the community service team. From the results of this dedication, it can be concluded that the existence of cultural heritage objects in the city of Semarang can still be maintained, by creating cultural heritage zones, and protection of cultural heritage objects in addition to using laws, will be more effective when using local regulations and empowering society in the economic field. Then the advice given is that the Semarang City government should make a policy that protects cultural heritage objects from business interests. Besides that, it is necessary to conduct socialization about the importance of cultural heritage objects for improving the welfare of the community.